Storage, patterns and controls of soil organic carbon in the alpine shrubland in the Three Rivers Source Region on the Qinghai-Tibetan Plateau - Nie, Xiuqing; Yang, Lucun; Li, Fan; Xiong, Feng; Li, Changbin; Zhou, Guoying (Catena (Giessen), 2019)
Alpine shrubland ecosystems in the Three Rivers Source Region (TRSR) store substantial soil organic carbon (SOC), but the storage, patterns and control of SOC in those ecosystems have rarely been investigated. In this study, using data from 66 soil profiles surveyed from 22 sites between 2011 and 2013, we estimated the storage and patterns of SOC, and their relationships with climatic factors, elevation, ground cover and slope. Our results showed that SOC storage in the top 100 cm across the TRSR shrubland was 0.68 ± 0.38 Pg C, with an average SOC density (soil carbon storage per area) of 26.21 ± 14.58 kg m−2. Spatially, SOC density increased with longitude and latitude. Vertically, SOC in the topsoil at 30 cm and 50 cm accounted for 56% and 75%, respectively, of the total at 100 cm. SOC density showed a decreasing trend with increasing elevation, but it was greater in regions of higher ground cover. The density had no relationship with either mean annual precipitation or slope. Increasing mean annual temperature had positive effects on SOC density, which is inconsistent with the global trend. With increasing soil depth, however, the effects of temperature on SOC density were not significant. Therefore, in a global warming scenario, increasing temperature gives shrubland considerable C sink potential on the topsoil, and the regions of C sequestration differ as a result of uneven increases in temperature. Hence, further monitoring of dynamic changes is necessary to provide a more accurate assessment of potential C sequestration in TRSR shrubland. •Storage and patterns of SOC were investigated in the TRSR shrubland.•SOC has no relationship with both precipitation and slope.•SOC was decreasing with elevation, but larger with both ground cover and temperature.